2022
DOI: 10.51709/9951272/summer2022/1
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perspectives towards Online Professional Development Programs during the Period of COVID-19 Pandemic in the Saudi EFL Context

Abstract: This study aimed to explore a group of teachers' perspectives on the effectiveness of online professional development programs in the Saudi English context. To achieve this main research objective, a five-point Likert scale with 21 items belonging to four essential dimensions was carried out on 537 English teachers using the snowball sampling method. The data was collected online through a Google Form-generated link. The study's findings revealed that English teachers' perceptions of the effectiveness of onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the findings of this study can inform the development of teacher training programs and professional development opportunities for EFL teachers in Saudi Arabia. By understanding the benefits of project-based learning and how it can be effectively implemented in EFL classrooms, teachers can enhance their teaching practices and improve their students' learning outcomes (Al-khresheh et al,2022;Alsamani & Daif-Allah, 2016) In answering the research question of this study, "What are the benefits of multimodal project-based learning in teaching English to international students in higher education institutions in Saudi Arabia? ", the results indicate that multimodal project-based learning can enhance language learning by incorporating multiple modes of communication, such as visual, auditory, and kinesthetic, and by promoting collaboration and critical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the findings of this study can inform the development of teacher training programs and professional development opportunities for EFL teachers in Saudi Arabia. By understanding the benefits of project-based learning and how it can be effectively implemented in EFL classrooms, teachers can enhance their teaching practices and improve their students' learning outcomes (Al-khresheh et al,2022;Alsamani & Daif-Allah, 2016) In answering the research question of this study, "What are the benefits of multimodal project-based learning in teaching English to international students in higher education institutions in Saudi Arabia? ", the results indicate that multimodal project-based learning can enhance language learning by incorporating multiple modes of communication, such as visual, auditory, and kinesthetic, and by promoting collaboration and critical thinking.…”
Section: Discussionmentioning
confidence: 99%
“…According to Niessen, Swarowsky and Leiz, cognitive ability declines as increasing age and this can have a negative impact on employees' self-efficacy to deal effectively with new task demands and services (Niessen, Swarowsky, & Leiz, 2010). Research by Al-khresheh, Mohamed and Asif (2022) showed that lecturers between the ages of 31 and 40 years old, if they are fully equipped with instructions, have basic training and have experience in technology, they will adapt better to the use of technology in teaching (Al-khresheh, Mohamed, & Asif, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…demands of each kid and modify their therapy accordingly. Speech therapists should make an investment in continuing education opportunities to foster a more successful therapeutic environment for their patients (Al-Khresheh et al, 2022;Andersson et al, 2022).…”
Section: Volume 38mentioning
confidence: 99%